Estudo comparativo de suco de uva e vinho tinto em parâmetros bioquímicos e de estresse oxidativo in vivo e em humanos - Copetti, Cristiane (2017)
Phenolic compounds are the major sources of antioxidants consumed in the human diet and are widely distributed in grapes and their by-products. Among these compounds are the flavonoids (catechin, epicatechin, quercetin, anthocyanins and procyanidins) and resveratrol (3,5,4-trihydroxy-stilbene), which are mainly found in grape products. Several in vitro studies in animal and human models have been demonstrating that these compounds have antioxidant action and improve lipid metabolism. However, the phenolic compounds present in red wine and grape juice show differences in their composition and quantity. The objective of the present study was to evaluate the effect of the acute consumption of grape juice and red wine from two cultivars on the biomarkers of oxidative stress in healthy individuals and the antioxidant effect in vitro. This intervention study, characterized as a crossover clinical trial, used grape juice, red wine and water (control), where healthy volunteers were evaluated before and after consumption, associated or not with a meal. Each subject was submitted to the procedure described above, three times with a one-week interval between each procedure, receiving at each of the three treatments. The blood was used for biochemical analysis and antioxidant potential. In addition to this, SH-SY5Y neural cells were induced to oxidative stress with the addition of hydrogen peroxide and added to different concentrations of juice and wine in order to test the antioxidant potential of the beverages. The results showed that great amount of phenolic compounds found in the samples of grape juice and wine contributed to the high in vitro antioxidant potential of these beverages. In addition, in vitro antioxidant capacity can be reproduced in vivo following acute ingestion by healthy subjects, consumption of Bordo juice and wine improved antioxidant capacity and reduced lipid oxidation in healthy volunteers. Juice and wine were able to lower glucose levels and only wine increased uric acid levels. Likewise, the wine had no antioxidant effect on the cell culture showing to be toxic in high concentration, while the juice had antioxidant effects against the cellular oxidative stress induced by H2O2. Grape juice and wine can be used to improve health and as a preventive for diseases related to oxidative stress, but wine should be consumed in smaller doses due to the pro-oxidant effect observed in cell culture.